EFFECT OF ELECTRON IRRADIATION CONDITIONS ON THE EFFICIENCY OF DEFECT FORMATION IN MgAl2 O4 SPINEL - Kazarinov, Yu.H.; Pop, O.M.; Megela, I.G.; Popov, Anatoli I. (Natsional'nyi Nauchnyi Tsentr, 2022)
The efficiency of defect formation in spinel ceramics of magnesium aluminate (MgAl2O4) under electron irradiation has been determined. A strong effect of cooling on the concentration of residual defects was revealed. When using electrons with energies above the giant dipole resonance for Mg, Al, O and cooling the sample with an air-blown aluminum radiator, a total increase in the efficiency of F-center formation by a factor of 4.3 was obtained. PACS: 61.72.jn; 61.80.Fe. © 2022, National Science Center, Kharkov Institute of Physics and Technology. All rights reserved.
This work was partially supported by the Ministry of Education and Science of Ukraine (Joint Ukrainian – Latvian Project № М/7-2022). The authors are grateful to Ivar E. Reimanis of Colorado School of Mine who provided samples of spinel ceramics. And IEP and IHEPNP high energy electron beam irradiation facilities operators for ensuring stable experimental accelerator beam modes.
Keywords: Research Subject Categories::NATURAL SCIENCES